Can Participatory Irrigation Management be an answer to Sustainable Irrigation Water Management? A case study from India - Giri, Saigdha; Chattopadhyay, Subhra (International Socioeconomic Review, 2024)
Participation of the communities at various tiers of irrigation management has gained popularity over the years. A parallel urge has been the promotion of sustainable practices that can provide high resource efficiency and greater returns with smaller resource outlay. Though studies have focused on both the issues, few have tried to link both. This study attempts to add to the existing knowledge by exploring whether sustainable management of irrigation can be achieved with the inclusion of farmers themselves in the operation and management of irrigation. For these 250 farmers who are members of Water Users Associations (WUAs) and 120 farmers who have never been a part of any WUA have been interviewed using Focus Group Discussion. Relative Irrigation Supply (RIS) and Irrigation Water Productivity (IWP) calculated using the CROPWAT 8.0 software of FAO, have been selected as the indicators of sustainability. Results show that the RIS among the participant farmers is lower than the non-participant farmers. The variability in RIS between the groups is statistically significant at p<0.05. The IWP is higher among the participant farmers and lower among the non-participants. The variance in IWP between the groups is not significant statistically. The strict adherence to water fees payment and training on rationed water use has imbibed water saving practices among the participant farmers. Thus, the study indicates that Participatory Irrigation Management can sustainability of irrigation practices among users and hence establishes a link between sustainable irrigation practice and community participation.